Efficacy and Safety of Continuous Infusion of Vancomycin in Children: A Systematic Review - Marta Alonso-Moreno; Marta Mejías-Trueba; Laura Herrera-Hidalgo; Walter Alfredo Goycochea-Valdivia; María Victoria Gil-Navarro (MDPI AG, 2021)
Vancomycin is used to treat a wide variety of infections within the pediatric population. In adults, continuous infusion of vancomycin (CIV) has been evaluated as an alternative to intermittent infusion of vancomycin (IIV) with potential advantages. In children, the use of CIV is increasing; however, data is currently limited. The objective is to provide efficacy and safety evidence for CIV within this population. The review was carried out following PRISMA guidelines. A bibliographic search was performed for studies on PubMed and EMBASE. Clinical trials and observational studies that reported clinical efficacy and/or target attainment of CIV in pediatrics were included. Articles were reviewed to assess their design and target population, characteristics of vancomycin treatment and the main findings in terms of safety and efficacy. A total of 359 articles were identified, of which seven met the inclusion criteria. All of them evaluated the target attainment, six assessed safety but only three assessed clinical efficacy. The best administration method for this antibiotic within the pediatric population is still unknown due to limited evidence. However, studies conducted thus far suggest pharmacokinetic advantages for CIV. Further investigation is required, in particular for studies comparing IIV with CIV for clinical efficacy and toxicity outcomes.